Improving Inclusive Education through Universal Design for Learning - Galkiene, Alvyra; Monkeviciene, Ona (Inclusive Learning and Educational Equity,, 2021)
This open access international scientific study provides an analysis of how the educational strategy of Universal Design for Learning can stimulate the process of inclusive education in different educational-cultural contexts and different areas of the educational system. The findings of the research deepen the conception of inclusive education and present an analysis of factors that are significant for developing the educational system as well as providing evidence-based recommendations for educational practice. The research for this work was done in four European countries with various historical-cultural contexts: Lithuania and Poland underwent a transformation of the educational systems at the turning point in their political system, shifting from a strictly centralized Soviet policy to a liberal and democratic education system; Austria has experienced changes in social stratification and a need for cultural harmonisation arising from active national migration processes, whereas Finland has been gradually developing a socio-democratic model of national welfare. The analysis of the educational processes in the four countries has been performed using a qualitative action research method. The researchers, in cooperation with the teachers from the selected schools in their country, have implemented the strategy of Universal Design for Learning and assessed its transformation indicators in terms of the quality of inclusive education components. .